Deposition rate and optical emissions in niobium oxide processes by reactive sputtering - Saccoman, João [UNESP]; Neto, Nilton Francelosi A. [UNESP]; da Silva, José H. D. [UNESP] (American Vacuum Society, 2024)
Niobium oxide films find various applications, such as antireflective optical layers, gas sensors, and solar cells. They also show promise for emerging applications such as electrochromic and photocatalytic devices. In order to optimize the deposition of niobium oxide films by RF reactive sputtering, a detailed investigation of the plasma parameters was performed. A pure metallic target and a mixture of Ar and O2 in different proportions were used in the experiments. The deposition power was varied between 120 and 260 W, while the total pressure was kept at 0.67 Pa throughout. Deposition rates, discharge self-bias voltage, and plasma optical emissions were monitored and analyzed. Additionally, computer simulations of the process utilizing existing models were conducted and a comparative analysis with the experimental results was performed. The main findings include mapping the deposition conditions as functions of oxygen flow rate. The flow ranges in which the deposition regime changes from metallic to oxygen contaminated target conditions were identified. The narrow O2 flow range associated with the regime changes was characterized by significant changes in the self-bias voltages and plasma emissions from oxygen, argon, and niobium. The observations evidence the importance of the detailed analysis of the deposition process to get the desired stoichiometry and optimized film properties.